The effectiveness of social support interventions on loneliness among older people in the community: a meta-analysis of randomised controlled trials - Huang, Guangting; Yang, Xiaotong; Yao, Li; Li, Xiaofang; Wu, Yuanping; Zhou, Shiqi; Wang, Yinhua (Frontiers in Aging, 2026)
BackgroundTo combat loneliness among elderly individuals, it is crucial to identify effective strategies that can alleviate the negative impact of loneliness on their overall well-being.ObjectiveThis study evaluated social support programs’ impact on loneliness in community-dwelling older adults. The goal was to inform tailored interventions that decrease loneliness and improve quality of life.MethodsWe systematically searched ten electronic databases (EMBASE, PubMed, Cochrane Library, Web of Science, CNKI, Weipu, WanFang, CBM) from inception to December 31, 2023, with citation chasing. Included randomized controlled trials (RCTs) tested social support interventions for loneliness reduction. Two independent reviewers extracted participant details, study characteristics, interventions, and outcomes. The methodological rigor of the included studies was assessed by JBI critical appraisal checklists.ResultsNineteen studies met inclusion criteria, with over half from China (n = 7) and the United States (n = 4). Meta-analysis showed that social support helped alleviate loneliness and the difference was statistically significant [SMD = −0.60, 95%CI (−1.00, −0.20), I2 = 93%, P = 0.003, random effect model]. Subgroup analysis showed significantly lower loneliness scores in experimental groups at less than 3 months [SMD = −0.68, 95%CI (−1.31, −0.06), I2 = 93%, P = 0.03, random effect model]. In addition, multiple-intervention groups also showed significantly lower scores versus controls. The combined result was [SMD = −1.26, 95%CI (−2.20, −0.32), I2 = 97%, P = 0.008, random effect model].ConclusionSocial support interventions effectively reduce loneliness among community-dwelling older adults. For practical application, community health professionals are encouraged to implement short-term (≤3 months) multicomponent programs that combine emotional, peer, and technological support, delivered through group counseling, tele-support, or structured social activities. Integrating these interventions into routine community nursing services and local age-friendly programs may enhance mental wellbeing and social connectedness among older adults.